Godaan Seorang Imam dalam Pelayanan menurut Yohanes Krisostomus - Hendi Hendi; Sesilina Gulo (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. This article discussed how a priest (church elder or overseer) can overcome worldly temptations through three spiritual disciplines or ascesis: prayer, fasting, and inner guarding. This article used the analytical and argumentative methods in literature written by John Chrysostom in his book "On the Priesthood" and the writings of the Church Fathers to contribute to the ministry of a priest. These three points of ascesis produce a holiness which makes him more Christlike. First, through prayer a priest can practice defeating the temptations and passions that arise from within his soul. Second, through fasting he is trained to overcome the temptations and passions that arise from the body or the flesh. Third, through inner vigilance (nepsis) he will be able to overcome the temptations of Satan who has continually seduced humans throughout the ages. These three asceses are aimed at bringing and guiding a priest to live a holy life, that is, against the desires of the flesh or worldly temptations and to produce good fruits that can be practiced in the ministry and society.Abstrak. Artikel ini mengkaji tentang cara seorang imam (penatua atau pengawas gereja) dalam mengatasi godaan-godaan duniawi melalui tiga disiplin rohani atau askesis: doa, puasa, dan keberjagaan batin. Artikel ini menggunakan metode analistis dan argumentatif di dalam literatur yang ditulis oleh Yohanes Krisostomus dalam bukunya “On The Priesthood” dan tulisan para Bapa-bapa Gereja untuk memberikan kontribusi bagi pelayanan seorang imam. Ketiga pokok askesis ini menghasilkan kekudusan yang semakin menyempurnakan dia menjadi serupa Kristus. Pertama, melalui doa seorang imam dapat berlatih mengalahkan godaan dan nafsu yang timbul dari dalam jiwanya. Kedua, melalui puasa dia dilatih untuk mengalahkan godaan dan nafsu yang timbul dari tubuh atau daging. Ketiga, melalui keberjagaan batin (nepsis) dia akan bisa mengatasi godaan dari Iblis yang senantiasa tanpa henti menggoda manusia di sepanjang zaman. Ketiga askesis ini bertujuan membawa dan menuntun seorang imam untuk hidup kudus yaitu melawan keinginan daging atau godaan-godaan duniawi dan menghasilkan buah-buah kebajikan yang bisa dipraktikkan di pelayanan dan masyarakat.